Teacher And Student Perception Of Learning English Via Online During The Covid-19 Outbreak At Smpn 1 Gondang - Kaviota, Dea; Mustofa, Ali; Setiawan, Slamet (EduInovasi: Journal of Basic Educational Studies, 2024)
To prevent the life-threatening transmission of COVID-19, the Indonesian government requires educational institutions across the country to switch to online learning. These contactless meetings ensure that teaching and learning activities continue as they should be. The current research sought to find out what challenges teachers and students faced while online learning was applied and how they perceived the method. A total of three students and three teachers from SMPN 1 Gondang, Mojokerto, were interviewed to share their views on online learning. The researcher used guided questions to explore the participants’ responses. From the data collected, technological barriers and demotivation are common challenges faced by teachers and students of SMPN 1 Gondang, Mojokerto, in organizing and participating in online classes. Although they favored the flexibility, they cultivated rather negative views of it. Several recommendations have been made to address these issues, ranging from improving the school’s digital infrastructure, organizing training programs to fill literacy gaps, and encouraging parents to establish an effective learning environment for students, ensuring they can keep up with the classes.